2011
DOI: 10.1590/s0100-69912011000500010
|View full text |Cite
|
Sign up to set email alerts
|

Estudo anatômico das duas bandas do ligamento cruzado anterior com o joelho em 90º de flexão

Abstract: OBJETIVO: Avaliar anatomicamente a origem femoral e inserção tibial das bandas ântero-medial e póstero-lateral do ligamento cruzado anterior. MÉTODOS: Estudados oito joelhos de cadáveres, foram feitas as seguintes medidas no fêmur: distância do centro da banda ântero-medial à cartilagem profunda e a ao teto. Ainda no fêmur, do centro da banda póstero-lateral à cartilagem profunda, a cartilagem inferior e à cartilagem superficial. Na tíbia, foi aferido do bordo ósseo tibial anterior à região anterior da banda â… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…The center of the tibial insertion of the AM bundle is approximately 20mm from the anterior edge of the tibia and from the PL bundle to 30mm. The distance between the center of the origin of the PL bundle to the lower cartilage is close to 5mm 10 .…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The center of the tibial insertion of the AM bundle is approximately 20mm from the anterior edge of the tibia and from the PL bundle to 30mm. The distance between the center of the origin of the PL bundle to the lower cartilage is close to 5mm 10 .…”
Section: Discussionmentioning
confidence: 74%
“…The ligament is extrassinovial and intraarticular composed of fibers that go from the anterior intercondylar region of the proximal tibia to the medial femoral condyle inside the intercondylar groove 9 . They have a main stabilizer function to the anterior tibial translation and secondary involvement in the restriction of the knee internal rotation 10 . In the study of Śmigielski that analyzed the anatomical structure of LCA of 111 knees of human cadavers, found that the femoral insertion and medial portion of LCA were thinner than previously and also determined the width of 11-17 mm and a thickness of about 3 mm 11 .…”
Section: Discussionmentioning
confidence: 99%
“… 8 In the present study, the anatomical measurements were made with the knee flexed at 90°, with the intention of increasing the applicability of the study to arthroscopic procedures. 6 Even with similar measurements, the results may show discrepancies if obtained in different manners. 7 , 8 …”
Section: Discussionmentioning
confidence: 97%
“…This may be because most studies have been conducted with the knee in the anatomical position (extension), whereas the surgical procedure is performed with the knee flexed. 6 , 7 , 8 The aim of this study was analyze the anatomy of the PCL and define objective anatomical parameters with the knee flexed at 90°.…”
Section: Introductionmentioning
confidence: 99%
“…Although the reconstruction is done with a single band, anatomical studies show that the ACL consists of two bands, one anteromedial and one posterolateral 2,3 .…”
Section: Introductionmentioning
confidence: 99%